Estimación de la calidad de agua del Río Quingeo, Cuenca, Azuay, mediante análisis de bioindicadores en el periodo 2021-2022 - Garcia Campoverde, Julio Cesar (2022)
Rivers are one of the principal water reserves for living beings, and they are also the habitat of aquatic organisms; however, their quality is threatened by anthropogenic activities. In this sense, this research aims to evaluate the water quality of the Quingeo river Cuenca city in Azuay province through the analysis of bioindicators (macroinvertebrates) and physicochemical, microbiological parameters. So, four samplings were carried out in four points (P01 Pillachiquir, P02 Capicorral, P03 Macas, P04 Quingeo center) from November to January using the landing net, a total of 5859 species distributed in 21 families were collected, and subsequently, the quality indices EPT, BMWP/COL, ABI and Shannon - Weaver were determined. Additionally, the following physicochemical and microbiological parameters were analyzed and compared: pH, dissolved oxygen, water temperature, total dissolved solids, electrical conductivity, total coliforms, fecal coliforms, BOD5, COD, nitrates, and turbidity, according to the Ministerial Agreement 097 A, annex TULSMA Book VI, Annex I; Table 3. Water quality criteria for agricultural irrigation and table 5. Water quality criteria for livestock use. It was evidenced that the Quingeo parish wastewater treatment plants are operational but not functional, which represents a significant problem for the area. Therefore, this research project proposes diagnosing water quality through physicochemical and microbiological analyses and comparing the results obtained from bioindicators with physicochemical and microbiological analyses. The results show a poor water quality for the EPT index and regular water quality for the ABI index; the BMWP/Col biological index indicated an acceptable water quality at point P01 while, in the other points, there is questionable water quality, and the Shannon-Weaver index revealed values of: 1.49 in Pillachiquir, 0.93 in Capicorral, 1.3 in Macas and 1.14 in Quingeo center, showing low diversity in the four points. In the case of the analysis of the physicochemical and microbiological parameters, it was determined that the water quality of the micro-basin is suitable only for agricultural irrigation and livestock use according to Ministerial Agreement 097 A. On the other hand, it is recommended that the population promote the proper functioning of the treatment plants to the respective department in charge of sanitation to improve the quality of life and minimize the pollution caused by discharges into the river.